Analisis Resepsi Khalayak Terhadap Isi Pesan Pada Iklan Wardah Cosmetics “Long Lasting Lipstic Feel The Color” - Sri Hesti Meilasari; Umaimah Wahid (Universitas Bina Sarana Informatika, 2020)
Each company has their own market segmentation for their offered product or services. Competition with the similar product is another challenge for the company itself to reach widely audience and get the segmented market. Advertisement as a part of an Integrated Marketing Communication is one of the marketing tools in bussiness to communicate with the wider community to introduce their products to audience. Advertisement in television has a certain message through its words or picture shown for their market. Wardah cosmetics as a cosmetis company which known has market segmentation for Moslem Woman try to make a moslem woman to appear attractively through their advertisement. Moslem woman in general has a standard common value to dress up in modesty. This research try to find out how's the audience's reception especially moslem woman at area of WTC Sudirman's Office as part of central business in Jakarta whom come from various background on the content of message Wardah Cosmetics Advertisement “Long Lasting Lipstic Feel The Color”. This research uses constructivis paradigm, namely, the truth of social reality can not be generalized to all people and seen as result of social construction of the audience, localy and specific. The researcher uses reception analysis method by conducting interview to informan choosen based on certain criteria. This research uses theory of Encoding-Decoding by Stuart Hall. Based on this research, there are 2 categories only which appears, Dominant Hegemonic and Negotiated Reading, also appears a new social value brought by milenials generation as a moslem woman “Jaman Now”.